Effect of plant density on selection for seed yield in two population types of Phaseolus vulgaris L - Singh, Shree P.; Guiterrez, JA (1990)
Pedigree selection for seed yield, using early generation yield tests, was practiced from the F2 to F7 in two populations of common bean (Phaseolus vulgaris L.) in three plant densities: 66, 133, and 266 thousand plants ha-1 at CIAT-Palmira, Colombia. The six highest yielding lines selected from each plant-density, along with 13 parents, were evaluated in a 7×7 lattice design with three replications at the three densities utilized for selection, and at 399,000 plants ha-1 in 1988 and 1989. Based on the mean performance of selected lines and the mean of the parents, selection for seed yield was effective in all densities in both populations. However, none of the lines selected from the population within the race Mesoamerica (TC 4673) significantly outyielded their best parent under any plant density. The highest yielding lines selected from the interracial population (TR 4635) outyielded their best parent irrespective of the plant-density used for selection. The highest yielding line originated from the highest density used for selection. Low density was neither good for selection nor for evaluation and identification of high-yielding cultivars of common bean. There was no significant difference between the mean yield of lines selected at the intermediate and high population densities. The effects of plant density, year, and their interactions were significant for seed yield.